Perilaku Kelompok Tani Padi Sawah dalam Mengatasi Kelangkaan Pupuk Bersubsidi di Kecamatan Trimurjo, Kabupaten Lampung Tengah, Provinsi Lampung - Fauziah Yulia Adriyani; Tubagus Hasanudin; Kordiyana K Rangga (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
The limitations of subsidized fertilizers have an impact on lowland rice production. This study aims to analyze the behavior of rice farmer group in overcoming the scarcity of subsidized fertilizers. The research was conducted in April-May 2022 in Trimurjo District, Central Lampung Regency. Respondent are some organizer in 15 rice farmers group that is chosen by using stratified random sampling technique. Data was collected through interviews using structured questionnaires to 15 samples of rice farmer groups. The analysis data was done descriptively. The results show that there are differences in farmers group behavior to overcome the scarcity of subsidized fertilizers. Beginner and upper class of farmer groups have moderate to skills and attitudes, but have not been able to facilitate their members in overcoming the scarcity of subsidized fertilizers while intermediate class of farmer groups have very good behavior that is demonstrated by the ability of farmer groups to look for subsidized fertilizers, to collaborate with alternative fertilizer producers and to produce organic fertilizers as an alternative to supplying fertilizers. It is important for government to improve agriculture extension role as facilitator in order to increase the capability of farmer’s group in overcoming the scarcity of subsidized fertilizers.